P96The aortic root phenotype in bicuspid aortic valve disease: evidence of shared Smad2 activation in aortic regions of distinct embryologic origin. (15th July 2014) - Prapa, S; Mccarthy, KP; Krexi, D; Gatzoulis, MA; Ho, SY
Abstract: Background: Transforming growth factor-b (TGFb) signalling plays a central role in vascular remodelling and aneurysm formation. A hypothesis of lineage-specific capacity in TGFb responsiveness has recently emerged which may explain the different aortopathy patterns in bicuspid aortic valve (BAV) disease. We aimed to assess the degree of histological abnormalities and TGFb activation in the BAV mesoderm-derived aortic root and ectoderm-derived ascending aorta. Methods: Aortic tissues from BAV patients and controls sampled at the level of sinuses of Valsalva and distal ascending aorta were examined via light microscopy for histological abnormalities and nuclear phosphorylated Smad2 (pSmad2) signalling, a marker of TGFb activation. A detailed histology grading score was used to assess the severity of medial wall abnormalities. Immunohistochemical data was expressed as the percentage of positive pSmad2 nuclei in each aortic wall layer. Results: Aortic specimens collected during surgery from 18 BAV patients (median age 22.5 [2–39]) were compared to 12 age-matched controls. Paired analysis in BAV patients reported a higher cumulative histology grading score in the ascending aorta compared to the root (5.5, [2-9] versus 4, [2-7]; p=0.004), which was persistently greater in patients with regurgitant valve disease (6, [2-9] versus 4, [2-6]; p=0.026), and in patients with aortic root dilatation (6, [3-9] versus 4, [2-6]; p=0.029). At immunohistochemistry, pSmad2 signalling was significantly higher in the BAV media compared to controls, both in the aortic root (38.7 [14- 61] versus 10.7 (2-36), p<0.001) and in the ascending aorta (40.3 [4-54] versus 7.9 [3-46], p=0.001). Medial pSmad2 activation did not differ significantly between the ascending aorta and root of BAV patients, with or without respective aortic dilatation. In the overall population, a positive correlation was noticed between the degree of pSmad2 signalling in the media and the severity of medial wall abnormalities, both in the aortic root (ρ=0.57; p=0.001) and the ascending aorta (ρ=0.6; p<0.001). Conclusion: The dilated aortic root phenotype may represent the primarily genetic form of BAV disease as patients with either root dilatation and/or predominant regurgitant valve disease had greater levels of medial wall degeneration in their ascending aorta. Enhanced TGFb signalling appears to play a key role in BAV aortopathy. The presence of increased pSmad2 activation in non-dilated BAV aortic segments points to a genetic trigger, with no differences in signalling between the mesoderm-derived root and the ectoderm-derived ascending aorta.